Повышение зонной избирательности электромагнитных кристаллов - Nazarko, A. I.; Timofeeva, Ju. F.; Nelin, E. A.; Popsuj, V. I. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The estimation of crystal-like structures band selectivity is considered. Methods of increasing of electromagnetic crystal’s selectivity are proposed. The experimental and theoretical characteristics illustrating possibility of substantial improvement of spectral properties of such structures are presented.